Modelling time-to-discontinuation of exclusive breastfeeding: analysis of infants and under-2 survival in Nigeria (2020)
Background: Regardless of national and international strategies towards promoting exclusive breastfeeding, only 17% and 35% of infants were exclusively breastfed in 2015 in Nigeria and Worldwide respectively. Therefore, we aim to estimate average length of exclusive breastfeeding for infants and under-2, evaluate and predict maternal impact. Data Source and Methods: This retrospective cross-sectional study applied NARHS data collected via multistage-cluster random sampling. Count and proportion quantified maternal characteristics, Kaplan- Meier method estimated length of exclusive breastfeeding whereas Cox Proportional Hazard model and Wald-test determine and evaluate maternal effect. Results: Median duration of exclusive breastfeeding was 6.0 months. Locality (P < 0.05 (0.73 -0.98)} and place-of-delivery (P < 0.01 (1.06-1.19)} were the determinant factors. Cox Proportional Hazard model fit the data and Wald-test identified main predictors. Conclusions: Average time at which exclusive breastfeeding was discontinued was six months, mothers' locality and delivery-place of infants influence exclusive breastfeeding duration in Nigeria. Hence, exclusive breastfeeding interventions should target those factors.